Partial Optimization of Endo-1, 4-Β-Xylanase Production by Aureobasidium pullulans Using Agro-Industrial Residues - Nasr, Shaghayegh (Mashhad University of Medical Sciences, 2013)
Objective(s) : Although bacteria and molds are the pioneering microorganisms for production of many enzymes, yet yeasts provide safe and reliable sources of enzymes with applications in food and feed. Materials and Methods: Single xylanase producer yeast was isolated from plant residues based on formation of transparent halo zones on xylan agar plates. The isolate showed much greater endo-1, 4-β-xylanase activity of 2.73 IU/ml after optimization of the initial extrinsic conditions. It was shown that the strain was also able to produce β-xylosidase (0.179 IU/ml) and α-arabinofuranosidase (0.063 IU/ml). Identification of the isolate was carried out and the endo-1, 4-β-xylanaseproduction by feeding the yeast cells on agro-industrial residues was optimized using one factor at a time approach. Results: The enzyme producer strain was identified as Aureobasidiumpullulans. Based on the optimization approach, an incubation time of 48 hr at 27°C, inoculum size of 2% (v/v), initial pH value of 4 and agitation rate of 90 rpm were found to be the optimal conditions for achieving maximum yield of the enzyme. Xylan, containing agricultural residues, was evaluated as low-cost alternative carbon source for production of xylanolytic enzymes. The production of xylanase enzyme in media containing wheat bran as the sole carbon source was very similar to that of the medium containing pure beechwoodxylan. Conclusion:This finding indicates the feasibility of growing of A. pullulans strain SN090 on wheat bran as an alternate economical substrate in order for reducing the costs of enzyme production and using this fortified agro-industrial byproduct in formulation of animal feed.